Situational analysis study for the agriculture sector in Kenya - Amwata, Dorothy A (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Agriculture is central to adaptation and mitigation of climate change. This is well recognized in the Paris Agreement, where many developing countries including Kenya prioritized agriculture as one of the critical sectors for the realization of their transformation to climate resilient development pathway. As part of commitment to achieve this, Kenya has embarked in developing its agriculture long-term strategy (LTS) to help define their longer-term agenda to guide near and long-term climate action and planning, while helping to guide updating of successive Nationally Determined Contributions (NDCs). To achieve this, a situational analysis of the agriculture sector was undertaken to provide a baseline. Both qualitative and quantitative approaches were employed in the study .These approaches includes document review and key stakeholder consultations which were used to establish the status, comprehensive trends, impacts of climate change, policies and strategies, adequacy of response measures and their coherence to existing policies, climate financing, measurement, reporting and verification, monitoring and evaluation frameworks in the sector in order to evaluate the progress made and identify the existing gaps to be addressed in order to transition Kenya’s agriculture sector to low emission, climate resilient development pathway. This analysis has established that Kenya has made significant the progress it modernizing and transforming it’s agriculture sector to an innovative, commercially oriented and competitive sector. This has been achieved through continuous review and operationalization of policies and strategies, enactment of laws and creation of institutions in the different agriculture sub-sectors. Other areas include implementation of policies, legislation, programmes and projects that aim to improve agricultural productivity, increase market access and household income, build social resilience and capacity building.